The Effect of Weathering on Color and Glossiness Properties of Polyurethane-Modified Water-Based Varnish Layers Applied to Thermally Treated Ash Wood - Göksel Ulay; Mete Akter; Nevzat Çakıcıer; Hüseyin Peker; Ümit Ayata; Abdi Atılgan; Seymen Çiftçi (BioResources, 2025)
The effects of artificial weathering (168, 336, and 504 h) on the glossiness values and color parameters of varnished, polyurethane-modified ash wood were investigated. Samples included control samples without treatment and thermally treated samples under two different conditions (190 °C for 1.5 h and 212 °C for 2 h), all coated with a polyurethane-modified water-based varnish. In non-thermally treated and varnished samples, decreases in L* values were observed after weathering, while increases were noted in ho, C*, b*, and glossiness at 60° in both perpendicular and parallel directions to the fibers. After weathering, for samples thermally treated at 190 °C for 1.5 h and varnished, increases were observed in glossiness values at 20° and 60° in both directions, as well as in L*, b*, and ho values. Conversely, decreases were noted in a* and C* values. In samples thermally treated at 212 °C for 2 h and varnished, increases in a*, L*, ho, b*, and C* values were detected after weathering, whereas decreases were observed in glossiness at all angles (20° and 60°) in both directions. The ∆E* values showed a decreasing trend in non-thermally treated varnished samples after weathering, while an increase was observed in samples thermally treated at 212 °C for 2 h and varnished.